Postgraduate Students’ Digital Literacy - Zannatul Israh; Siti Drivoka Sulistyaningrum (UICELL, 2022)
The rapid advancement of technology in the twenty-first century encouraged students to use communication tools and digital resources in their classroom learning activities. Some students must complete sophisticated tasks, so they must be able to manage files, including creating, editing, uploading videos, and using web-based tools. In order to complete those tasks in a satisfactory way, students must have good digital literacy. This study investigates postgraduate students’ digital literacy. The aim of this study is to explore postgraduate students’ digital literacy. The instruments used to gather data were a questionnaire and an interview. A total of 30 postgraduate students participated in this research. The finding was highlighted in terms of students’ ability to use computers, students’ internet skills, and students’ ability to seek and retrieve information and information resources. Key Words: Communication Tools, Digital Literacy, Postgraduate Students